2020
DOI: 10.1002/fsn3.1939
|View full text |Cite
|
Sign up to set email alerts
|

Improving gelatin‐based emulsion films with cold plasma using different gases

Abstract: Common packaging systems have the ability to delay the loss or adsorption of moisture between the food and the surrounding environment, but they cannot prevent the transport of moisture, fats, and other compounds inside the food package. Edible films and coatings can solve this problem. In addition, the addition of active compounds prevent spoilage of food, maintaining its quality during transportation and storage, and after decomposition, they are degraded to water, carbon dioxide, and inorganic compound in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…However high energy in the plasma and the longer treatment of film for 90 s decreased the compactness of the zein/chitosan composite, which resulted in a drop in TS and EAB. Ledari, Milani [78] reported that the application of cold plasma using O 2 , N 2 , air, Ar, and ethanol-argon gases alone cannot change the mechanical properties of gelatin films significantly.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However high energy in the plasma and the longer treatment of film for 90 s decreased the compactness of the zein/chitosan composite, which resulted in a drop in TS and EAB. Ledari, Milani [78] reported that the application of cold plasma using O 2 , N 2 , air, Ar, and ethanol-argon gases alone cannot change the mechanical properties of gelatin films significantly.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Apart from the plasma treatment time and voltage, types of plasma forming gases are also important factors that control the thermal stability of the biopolymer-based films. Ledari, Milani [78] carried out DSC of gelatin-corn oil emulsion-based films treated with O 2 , N 2 , air, Ar, and ethanol-argon (EtOH-Ar) plasma. The DSC analysis of these films showed that plasm treatment using different plasma forming gases had a different impact on the thermal properties like melting temperature (T m ) and melting enthalpy (∆H m ).…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to having high water solubility and the fact that it exhibits the sol–gel reaction at 35 °C, gelatin is useful as a hydrogel component because its mechanical and biochemical properties can be modified by cross-linking [ 17 , 18 , 19 ]. The cross-linking of gelatin was occasionally performed using chemical cross-linking using condensing agents (1-ethyl-3-[3-dimethylami-nopropyl]-carbodiimide hydrochloride (EDC)/N-hydroxysuccinimide (NHS) [ 20 ], glutaraldehyde (GTA) [ 21 ], or 4-[4,6-dimethoxy-1,3,5-triazin-2-yl]-4-methylmorpholinium chloride (DMT-MM) [ 22 ]), high-energy electron beams [ 23 ], γ-irradiation [ 24 ], plasma treatment [ 25 ], dehydrothermal treatment [ 26 ], or treatment with enzymes such as microbial transglutaminase [ 19 , 27 ].…”
Section: Introductionmentioning
confidence: 99%